2004
DOI: 10.1080/01431160412231269652
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination potential of X-band polarimetric SAR data

Abstract: In anticipation of X-band polarimetric Synthetic Aperture Radar (SAR) data from future sensors, we investigated the potential of X-band fully polarimetric data for discriminating between the principal classes present in a study site near Avignon, France. Decomposition and analysis techniques have been applied to a dataset acquired by the ONERA airborne RAMSES (Radar Aéroporté Multi-Spectral d'Etude des Signatures) SAR. Results show that Xband provides some discrimination capability. The polarimetric parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In contrast, the inversion accuracy of X-band SAR data with two incidence angles did not improve compared to the results of single incidence angle X-band SAR data [53]. This is due to the fact that the dependence of X-band SAR on surface roughness has been described as weak over agricultural areas [54,55]. Furthermore, Aubert et al showed that the sensitivity of the X-band SAR data to soil moisture is significant [56].…”
Section: Empirical Model Experimentsmentioning
confidence: 49%
“…In contrast, the inversion accuracy of X-band SAR data with two incidence angles did not improve compared to the results of single incidence angle X-band SAR data [53]. This is due to the fact that the dependence of X-band SAR on surface roughness has been described as weak over agricultural areas [54,55]. Furthermore, Aubert et al showed that the sensitivity of the X-band SAR data to soil moisture is significant [56].…”
Section: Empirical Model Experimentsmentioning
confidence: 49%
“…So far, most research in this field has been focused on the use of L-and C-band satellite SAR put in orbit by the international and national space agencies (European Space Agency, ESA, Japanese Aerospace Exploration Agency, JAXA, and National Aeronautics and Space Administration, NASA). With the advent of the recent TerraSAR-X and COSMO-SkyMed (CSK) missions much interest has been addressed in evaluating the potential of X-band in the various land applications [Baghdadi et al, 2004;Paris-Anguela et al, 2008]. A significant project, supported by the Italian Space Agency (ASI), for exploiting the capabilities of X-band SAR of the CSK mission in monitoring soil moisture, vegetation biomass and snow cover parameters was carried out in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out using synthetic aperture radar (SAR) data in the X-, C-, L-, and P-bands (e.g., Cloude and Pottier, 1996;Lee et al, 1999;Baghdadi et al, 2004;Touzi et al, 2004). Many studies have been carried out using synthetic aperture radar (SAR) data in the X-, C-, L-, and P-bands (e.g., Cloude and Pottier, 1996;Lee et al, 1999;Baghdadi et al, 2004;Touzi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%